A Systematic Literature Review Examining the Impact of Societal Factors on Student’s Intention to Enrol in Technical and Vocational Education and Training (TVET) Programs at the Tertiary Level - Mohd Nawi, Mohd Zulfakar; Ahmad, Nor Aziah; Muhammad Ghazali, Ameleya; Mohd Anuar, Muhammad Huzaifah (2024)
This study investigates the sociocultural influences on people's choices to participate in Technical and Vocational Education and Training (TVET) programmes, to comprehend the discrepancies in enrollment rates. A comprehensive literature analysis was undertaken from 2016 to 2023 utilising the PRISMA methodology, emphasising research analysing social factors influencing TVET enrollment intentions. Key sociocultural elements highlighted include the correlation between TVET and labour market demands, the perceived status of TVET programmes, and the influence of family and peer perspectives. Societal norms and misunderstandings regarding the economic results of Technical and Vocational Education and Training (TVET) graduates influence cultural preferences for conventional academic paths over vocational education. Nevertheless, data from areas with strong governmental and corporate backing for TVET suggests these beliefs may be changed. The study emphasises the need for more research on the evolution of social views, the impact of media campaigns, cross-cultural variations, and corporate influence on moulding perceptions of TVET. Improving comprehension and correcting misunderstandings about TVET may help stakeholders advance vocational education and develop a competent, flexible workforce. This research establishes the foundation for future efforts to increase TVET participation by engaging certain segments of society.